2017
DOI: 10.1016/j.crvi.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of human obesity: A comprehensive review

Abstract: Obesity and its related health complications is a major problem worldwide. Hypothalamus and their signalling molecules play a critical role in the intervening and coordination with energy balance and homeostasis. Genetic factors play a crucial role in determining an individual's predisposition to the weight gain and being obese. In the past few years, several genetic variants were identified as monogenic forms of human obesity having success over common polygenic forms. In the context of molecular genetics, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
162
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(186 citation statements)
references
References 230 publications
3
162
0
21
Order By: Relevance
“…Obesity is the result of many factors; therefore, it should be considered as a polygenic disease [15]. Obesity is characterized by many hormonal and metabolic features; however, to date, metabolic differences between obese and thin people cannot be unambiguously determined.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is the result of many factors; therefore, it should be considered as a polygenic disease [15]. Obesity is characterized by many hormonal and metabolic features; however, to date, metabolic differences between obese and thin people cannot be unambiguously determined.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007 three independent studies identified FTO as obesity susceptibility gene [810]. A number of different obesity-susceptible loci have been reported by the GWAS approach ( MC4R , MC3R , SLC6A14 , TMEM18 , POMC , BDNF , NEGR1 ) [11]. Among these findings, the biggest effect on obesity phenotype till date has the FTO .…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente se ha informado que existen alrededor de 127 sitios en el genoma humano relacionados con el desarrollo de la obesidad a través de los estudios de GWAS. (Singh, Kumar & Mahalingam, 2017) De acuerdo a Singh, la genética de la obesidad se puede dividir en dos grandes grupos. En el primero encontramos todos los Síndromes que se asocian con el desarrollo de obesidad con o sin retraso en el crecimiento, en el segundo la obesidad causada por la mutación de un solo gen o monogénica y la poligénica (Singh, 2017).…”
Section: Factores Genéticosunclassified
“…Las cuales juegan un rol importante comportamiento alimentario regulado por el hipotálamo del sistema nervioso central. (Singh, 2017).…”
Section: Factores Metabólicosunclassified
See 1 more Smart Citation